Maja Miše, Gnathia and Related Hellenistic Ware on the East Adriatic Coast - Kögler, Patricia (Journal of Hellenistic Pottery and Material Culture, 2017)
This volume is the revised and expanded version of Maja Miše’s (henceforth MM) Ph.D. dissertation, »Gnathia Ware on the East Adriatic Coast (from 4th to 1st c. BC)« (2010; Department of Archaeology, University of Zagreb, Croatia). The reason for the study is the abundance of Gnathia pottery at sites in the East Adriatic region, originating from South Italian as well as local workshops and contributing to the clarification of production issues and trade relations in the regions on both sides of the Adriatic Sea. As MM points out in the introduction, the primary aim of the publication is to give the Gnathia ware of the East Adriatic region greater scientific attention. This goal is already achieved by the publication of the finds and their analysis in an international language – English; making the material available to the research community in a satisfactory manner. Further objectives of the study are the definition of the local production of the city of Issa, the identification of additional workshops and the exploration of trade contacts and exchange mechanisms in the Adriatic region.